Model Pendidikan Agama Kristen Kontekstual Berdasarkan Markus 6:30–44 untuk Mendukung SDGs 2 di GBI Serafim Cengkareng Timur - Tan Siauw Fung; Eddy Suandar Simanjuntak; Wahju Astjarjo Rini (Sekolah Tinggi Teologi Ekumene Jakarta., 2025)
Issues of hunger and food security (SDG 2: Zero Hunger) are increasingly evident in urban areas, including Cengkareng Timur, West Jakarta. This condition highlights the need for more contextual and sustainable involvement of churches. This article aims to formulate a Contextual Christian Religious Education (CRE) Model based on the Gospel of Mark 6:30–44 as a strategy for empowering congregations to respond to local food vulnerability. This study employs a descriptive qualitative approach and was conducted at GBI Serafim Cengkareng Timur through the Berbagi Makan Siang Gratis food ministry program. Data were collected through interviews, observations, and documentation, and analyzed thematically. The findings indicate that Mark 6:30–44 contains key values—compassion, congregational participation, sharing practices, and the fulfillment of basic needs—which are relevant for moving Christian education from faith instruction toward social action. Based on these findings, this study formulates the R.O.T.I Model (Simple, Authentic, Transformative, and Implementative) as a contextual CRE model that encourages congregational engagement and supports the practical achievement of SDG 2.